Relationality of the Law: On the Legal Collisions in the Finnish Planning and Land Use Practices - Rannila Päivi (SAGE Publications Inc., 2022)
Nordic welfare state ideologies inform democratic and transparent land use and building practices. A closer examination reveals how variously these ideals are translated into practice. Finnish law strictly defines how building processes should proceed; however, a number of decisions still ignore the law, which can be seen in the complaints sent to the Administrative Courts. This paper examines the legality of Finnish land use processes through cases and interviews with judges. The findings suggest a need for a more critical spatio-legal analysis of planning that realizes the relationality of the law, and the invisible jurisdictions inherent in local decision making.